WEDDING IN THE MUNICIPALITY OF METKOVIC IN THE PERIOD BETWEEN 1890 TO 1918, BASAD ON THE REGISTER OF WEDDING - Dugandžić, Žarko (Politeia, 2017)
The work is based on the analysis and research on wedding registry of Metković municipality, i.e. wedding registry of parishes Metković, Dobranje,Vidonje and SlivnoRavno in the period between 1890 and 1918. The analysis of those sources provided space for the observation of the dynamics of weddings in the part of the Lower Poneretvalje. The frequency of weddings in Metkovic municipality is similar to the rest of Croatia. The maximum number of weddings is noted in February and January, whilst the minimum in December and March. Cousin marriages are more frequent in smaller communities. In this research such communities are parish Dobranje and Vidonje. The smallest number of such cases is in Metkovic which is much more open environment in comparasion to the other parish in municipality. In average, men would marry at 28.7, whereas woman at 24. The average age difference between men and women was from 4 to 6 years. Insignificant number of man got married under the age of 20 (2%). Regarding women, that numbet is slightly higher (11.01 %). Remarrying was more common amongst men(14,97%) than women (6,86%). In the period in question, value of the rate of nupciality goes: from 5,22 %. to 14,02%.in parish Metkovic; from 2,50%. to 8,70%.in parish Vidonje m 4,82%. to 10,40%. in parish Dobranje.